(untitled) (Journal of Engineering, 2018)
The present study addresses adopting the organic and nutritious materials in dairy wastewater as media for cultivation of microalgae, which represent an important source of renewable energy. This study was carried out through cultivation of three types of microalgae; Chlorella sp., Synechococcus, and Anabaena. The results shows the success the cultivation of the Synechococcus and Chlorella Sp, while the Anabaena microalgae were in low-growth level. The highest growth was in the Synechococcus farm, followed by Chlorella and Anabaena. However, the growth of Synechococcus required 10 days to achieve this increase that represents a negative indicator of the adoption of this type of microalgae in this media to meet the desired aims. While Chlorella needs less than two days to start growing. Moreover, the data obtained from the experiment show that removal of chemical oxygen demand in Chlorella cultures was (72%) more than that obtained from cultivation of other microalgae. Thus this microalgae is more efficient in wastewater treatment than other types.